Prevention of tooth discoloration associated with triple antibiotics - Bona Kim; Min-Ju Song; Su-Jung Shin; Jeong-Won Park (Korean Academy of Conservative Dentistry, 2013)
Regenerative endodontics has a potential to heal a partially necrotic pulp, which can be beneficial for the continued root development and strengthening of immature teeth. For this purpose, triple antibiotic mixture of ciprofloxacin, metronidazole, and minocycline was recommended as intracanal medicament in an attempt to disinfect the root canal system for revascularization of a tooth with a necrotic pulp. However, discoloration of the tooth was reported after applying this. This case shows the idea for preventing the tooth discoloration using a delivery syringe (SW-O-01, Shinwoo dental) to avoid the contact between the clinical crown and the antibiotics.